2018
DOI: 10.1002/2017jg004180
|View full text |Cite
|
Sign up to set email alerts
|

Sun‐Induced Chlorophyll Fluorescence, Photosynthesis, and Light Use Efficiency of a Soybean Field from Seasonally Continuous Measurements

Abstract: Recent development of sun‐induced chlorophyll fluorescence (SIF) technology is stimulating studies to remotely approximate canopy photosynthesis (measured as gross primary production, GPP). While multiple applications have advanced the empirical relationship between GPP and SIF, mechanistic understanding of this relationship is still limited. GPP:SIF relationship, using the standard light use efficiency framework, is determined by absorbed photosynthetically active radiation (APAR) and the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
118
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 78 publications
(122 reference statements)
14
118
3
3
Order By: Relevance
“…This implies that the spectral shape is quite stable and that all wavelength ranges respond to changes in variable PSII fluorescence yield driven by PQ and NPQ; (2) far‐red SIF is more closely correlated to photosynthesis and APAR than red SIF (Figures ), because it is less prone to re‐absorption by Chl at both leaf and canopy scales (Fournier et al, ; Yang & van der Tol, ). At the canopy scale, the strong correlation between SIF and APAR (Figures and ) confirms previous results in crop canopies (Miao et al, ; Yang et al, ), which makes intuitive sense since APAR covaries with seasonal changes in leaf area in these systems, and is prone to less error than calculated GPP fluxes; and (3) Since wavelengths in the far‐red spectrum are less impacted by confounding factors such as chlorophyll or canopy structure (Figure S12), current satellite retrievals in this region may be better suited to assess stress induced downregulation of photosynthesis than changes in the ChlF spectral shape alone.…”
Section: Discussionsupporting
confidence: 82%
“…This implies that the spectral shape is quite stable and that all wavelength ranges respond to changes in variable PSII fluorescence yield driven by PQ and NPQ; (2) far‐red SIF is more closely correlated to photosynthesis and APAR than red SIF (Figures ), because it is less prone to re‐absorption by Chl at both leaf and canopy scales (Fournier et al, ; Yang & van der Tol, ). At the canopy scale, the strong correlation between SIF and APAR (Figures and ) confirms previous results in crop canopies (Miao et al, ; Yang et al, ), which makes intuitive sense since APAR covaries with seasonal changes in leaf area in these systems, and is prone to less error than calculated GPP fluxes; and (3) Since wavelengths in the far‐red spectrum are less impacted by confounding factors such as chlorophyll or canopy structure (Figure S12), current satellite retrievals in this region may be better suited to assess stress induced downregulation of photosynthesis than changes in the ChlF spectral shape alone.…”
Section: Discussionsupporting
confidence: 82%
“…Radiative energy absorbed by chlorophyll molecules in excess of what can be used to carboxylate CO 2 , is either dissipated as heat or re-emitted as fluorescence 13 , which underlies the idea of inferring photosynthesis on the basis of measurements of chlorophyll fluorescence 28 . Even though the relationship between chlorophyll fluorescence and leaf photosynthesis is not unique 14 , tower- and satellite-based SIF measurements have been shown to scale with GPP as it changes during the season and/or with eco-climatological factors that govern the distribution of global biomes 15,17,18 . To a large degree, the explanatory power of these SIF-GPP relationships derives from the underlying significant changes in APAR across season and latitude 19 , which together with the light-use efficiency (LUE), determines GPP 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even though fluorescence competes for the same excitation energy as photosynthesis, their relationship is neither unique nor simple 14 . Nevertheless, SIF has been repeatedly demonstrated to scale with GPP across broad gradients in productivity 15,16 and/or along the seasonal cycle 17,18 , driven mainly by underlying large changes in the magnitude of absorbed photosynthetically active radiation (APAR) 19 . It remains to be demonstrated, however, how well ecosystem-scale SIF is able to track changes in GPP in situations when APAR is constant, but GPP declines in response to stress.…”
Section: Introductionmentioning
confidence: 99%
“…SIF has been found strongly correlated with the gross primary production (GPP) in a quasi‐linear pattern at large spatial and temporal scales (Frankenberg et al, ; Guanter et al, ; Li et al, ; Miao et al, ; Wood et al, ; Yang et al, ; K. Yang, Ryu, et al, ; Yang et al, ). Some studies suggest the potential of a universal GPP:SIF relationship across various biomes (Frankenberg et al, ; Li et al, ; Sun et al, ; but see Zhang et al, ), and others used SIF to constrain photosynthetic parameters (Guan et al, ; Perez‐Priego et al, ; Zhang et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that APAR is the primary driver that leads to the linear GPP:SIF relationship (Rossini et al, ; K. Yang, Ryu, et al, ; X. Yang, Shi, et al, ; Yang et al, ; Zhang et al, ). Some studies also suggested that LUE and SIF y contribute to the relationship and a diverse LUE:SIF y relationship implies a potentially diverse GPP:SIF relationship (Badgley et al, ; Miao et al, ; Wieneke et al, ). However, the contributions from PAR in , fPAR, LUE, and SIF y to GPP and SIF variations as well as the GPP:SIF relationship have not been specifically quantified and compared across a sufficiently wide range of conditions to provide a clear conclusion, and more studies of this issue are warranted.…”
Section: Introductionmentioning
confidence: 99%